Study on Prevention and Control of Confined Water Hazard in Deep Resource Exploitation: Scientific Basis of “GCD-D” Design - Yanbo Hu; Jiaze Xu; Qiqing Wang; Jingying Li; Qingguo Xu; Shuangfeng Guo (Geofluids, 2023)
Deep mining of resources has destroyed the stress balance of original rock, formed water gushing channel, and caused the outburst of confined water, thus causing disaster. At present, “Ground Controlled Directional Bedding Branch Drilling (GCD-D)” grouting has achieved remarkable results in controlling water disasters. However, “what is the scientific design principle of GCD-D?” This key scientific question has not yet been answered by systematic science. According to the regional engineering geology and hydrogeological conditions of North China-type coalfields, this study uses the methods of analogy, theoretical analysis, and model analysis to demonstrate and analyze and obtains six basic principles for the selection of the target layer for the layout of “GCD-D.” The design principle of “GCD-D” was put forward for the first time. The results can provide a scientific theoretical basis for the control of confined water disaster in deep mining of North China coalfields.